War’s Impact on Displacement, Migration, and Development in Ukraine - Luong, Hong Anh (2025)
This thesis investigates the multifaceted impact of the Russia-Ukraine war, which began in February 2022, on Ukraine’s demographic composition and regional economic development. It addresses two central research questions: (1) How has the war shaped internal displacement and migration patterns within Ukraine? and (2) How have demographic shifts in conflict-affected regions influenced regional economic performance? From a demographic perspective, the analysis reveals that the war has displaced more than 10.6 million individuals, comprising approximately 3.7 million internally displaced persons and 6.9 million refugees, predominantly from the eastern oblasts of Donetsk and Luhansk. This mass movement has led to significant population imbalances, placing considerable strain on public services and labor markets in both host and origin regions. From an economic perspective, the conflict has disrupted key sectors, particularly agriculture, where grain production declined by 41% between 2021 and 2022. These setbacks, alongside contractions in the services and energy sectors, reflect the broader decline of regional economic capacity. By combining demographic data with macroeconomic indicators, this study contributes to the growing literature on post-conflict recovery, forced migration, and economic resilience, offering insights for both policy design and academic discourse.